Access to healthcare for undocumented migrants in France: a critical examination of State Medical Assistance. Issue 1 (December 2016) - André, Jean-Marie; Azzedine, Fabienne
Abstract In France in 2012, of the total population of 65.2 million, 8.7 % were migrants. After being the third principal host country, France is now the 6th highest host country in the OECD. Since the 1980's numerous Acts have been passed by parliament on immigration issues. In 2000 the Universal Health Cover (Couverture Maladie Universelle) was created as health coverage for all residents of France. At the same time the State Medical Assistance (Aide Médicale de l'Etat) was created as health protection for undocumented migrants. Since the creation of this scheme, it has been the object of many political debates which call it into question, on account of its cost, perceived fraud, and the legitimacy of a social protection for undocumented migrants. Recently, access to State Medical Assistance has been made difficult by introducing conditions of residence and financial contributions. After a reports' analysis on institutional, associative, research studies and European recommendations, we note that all reports converge on the necessity of health protection for undocumented migrants. The major reasons are humanitarian, respect of European and International conventions, for public health, and financial. Moreover, fraud allegations have proved to be unfounded. Finally, State Medical Assistance is underused: in 2014 data from Médecins du Monde shows that only 10.2 % of undocumented migrant patients in their health facilities have access to this scheme. We conclude that the political debate concerning the State Medical Assistance should be about its under-utilisation, its improvement, its merger with the Universal Health Cover, and not its elimination. Moreover, the current debates regarding this scheme stigmatize this population, which is already precarious, making it more difficult for migrants to access healthcare, and generally, weaken national social cohesion.